Kebijakan Luar Negeri Amerika Serikat Tentang Pembatasan Imigran Muslim Era Pemerintahan Donald Trump - Hakim, M. Fathoni (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
There are two focus problems in this research. Which are: a). How does the securitization process of Muslim immigrant issues in the United States. b). What is the impact on criminal law? Donald Trump?In analyzing Donald Trump's foreign policy, researchers using foreign policy analysis from William D. Coplin that shares domestic and international factors, as well as the characteristics and nature of policymakers. In terms of domestic factors, it is found that the issue of Muslim immigrants in securitization becomes a security threat. The decline in economic and military capabilities also appears in this domestic factor. From the international side, emerging new US competitors, namely China. The rise of China's economic and military dimensions also lies behind this international factor. Domestic factors and international factors combined with Donald Trump's personality and character as an entrepreneur, have arrogant, narcissistic, overcommited and tend to be conservative. In this case the formulation of US foreign decisions about Restriction of immigrant muslim.